Analisis Beban Kerja Menggunakan Metode NASA-TLX Pada CV. Bahagia Jaya Alsindo - Anita Pramesti; Endang Suhendar (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2021)
CV Bahagia Jaya Alsindo is part of PT. Bahagia Jaya Sejahtera, a member of the Bahagia Jaya Group, is known as a producer of agricultural, industrial, agricultural, livestock and fishery equipment / machinery. Problems arising from the many demands of work from the company to the production operator that resulted in the production process not running optimally, there are indications of employee turnover and work space that is not comfortable so that makes employees feel stressed at work. This study aims to determine the workload of hammer mill machine production operators measuring and cutting materials, assembling, painting, and finishing good, to determine the factors that cause mental workload with employee turnover indications and to reduce the mental workload felt by hammer mill production operators. The method used in this study is NASA-TLX (Task Load Index) with two stages, namely the weighting stage and the grading stage. Initial research results obtained WWL (Weight Workload) operator part of the measurement and cutting materials by 73.56, the Assembling section by 76.00, the painting part by 72.00, and finishing good by 73.33 where the results experienced a mental workload high. Proposed improvement is done by holding psych tests, providing training, providing Personal Protective Equipment (PPE) while working and holding work shifts.